A hybrid solar‐RF energy harvesting system based on tree‐shaped antenna array. Issue 10 (9th July 2022) - Wang, Tao; Huang, Kama; Liu, Wenbo; Hou, Jing; Zhang, Zhuoyue
Abstract: In this article, the hybrid solar energy harvesting and wireless energy harvesting system is proposed. The hybrid energy harvesting system is comprised of the rectifiers, the solar cell panel, and the tree‐shaped antenna. The four tree‐shaped antennas are fabricated using three‐dimensional (3D) printing. The rectifiers are directly beneath the solar cell panel, and the every antenna connect to the corresponding rectifiers by the SMA adaptor. The key preponderance of this method is that the solar cell panel combined with the antenna to create multifunctional compact hybrid RF and solar energy harvesting system. Meanwhile, the four tree‐shaped antennas are used for enhancing the integral RF harvested energy. In addition to this, the 3D printed tree‐shaped antenna are nearly not affect on the sunshine received from the solar cell panel. It is demonstrated that in the lab, the maximum harvested power of the rectenna is 52.6% when the receiving RF power is 8 dBm, and the solar cell panel can achieve 7.3 mW power. The tree‐shaped antenna operates from 2.39 to 2.52 GHz for the reflection coefficient below −10 dB, and the peak gain is 6.0 dBi. Besides, when the RF input power is 8 dBm, the RF‐to‐DC conversion efficiency of the rectifier is 68.7%. The feasibility of the hybrid solar‐RF energy harvesting system used tree‐shaped antenna is demonstrated.